Defect Healing in FAPb(I1‐xBrx)3 Perovskites: Multifunctional Fluorinated Sulfonate Surfactant Anchoring Enables >21% Modules with Improved Operation Stability (Adv. Energy Mater. 20/2022). Issue 20 (26th May 2022) - Zhu, Jun; Qian, Yongteng; Li, Zijia; Gong, Oh Yeong; An, Zongfu; Liu, Qing; Choi, Jin Hyuk; Guo, He; Yoo, Pil Jin; Kim, Dong Hoe; Ahn, Tae Kyu; Han, Gill Sang; et al.
Abstract : Perovskite Solar Cells In article number 2200632, Gill Sang Han, Hyun Suk Jung and co‐workers report a defect healing strategy that enables the fabrication of highly efficient and stable perovskite large‐area solar cell modules. In addition, an exciting solar‐driven water‐splitting system is demonstrated using clean and renewable solar energy, which is expected to help to realize a carbon‐neutral economy and bring the hydrogen economy closer to reality.